Didactic criticism of the two works of Mohamed-Taghi Ghiassi, RaveŠe no dar āmuzeŠe zābān farānse (fifth edition 1993/1372) and Farānseje gām be gām (eighth edition 2013/1392) - Kamyar Abdoltajedini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this review, we have studied the teaching of Dr. Ghiassi through his works: New method to Teach French and French Step by Step. To do this, we first studied their content and form. To do this, we first checked the content and form of these works to derive exemptions from their strengths and weaknesses. Then, analyzing and comparing the author's remarks, in his introductions, with the principles of the known methods and teaching approaches we demonstrated that he adopts the grammar-translation method. In a final stage, we studied the quality of the content and Dr. Ghiassi’s teaching grammar, vocabulary, and pronunciation. In this last section, we have demonstrated that both books are rich in vocabulary. But, we also said that the content does not match the needs of the learners, the teaching of pronunciation is not effective, and sometimes the selected texts do not contain the grammatical points discussed.